2002
DOI: 10.1046/j.1365-2036.2002.01333.x
|View full text |Cite
|
Sign up to set email alerts
|

Foetal intrauterine growth restrictions with Helicobacter pylori infection

Abstract: SUMMARYBackground: Helicobacter pylori infection has been associated with growth restriction in young children. Aim: To determine whether there is an association between H. pylori infection and intrauterine growth restriction. Methods: Four hundred and forty-eight consecutive pregnant women (aged 15-44 years), attending for routine examinations in the third trimester, were enrolled. Clinical, demographic and previous obstetric data, as well as smoking history, were collected. At delivery, the weight, height, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
3
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 33 publications
1
56
3
1
Order By: Relevance
“…It is a common bacterial pathogen that colonizes the gastric mucosa in humans and induces chronic gastric inflammation. In pregnant women H. pylori infection can cause intrauterine fetal growth retardation (Eslick et al, 2002), increase the risk of reproductive disorders (Figura et al, 2002), and induce cerebral ischemia (Grau et al, 2001) and coronary heart disease (Pellicano et al, 1999). A screen of 50 patients with H. pylori infection has revealed 33.3% prevalence of anti-b2GPI antibodies (Sorice et al, 2000).…”
Section: Anti-b2gpi and Infectionmentioning
confidence: 99%
“…It is a common bacterial pathogen that colonizes the gastric mucosa in humans and induces chronic gastric inflammation. In pregnant women H. pylori infection can cause intrauterine fetal growth retardation (Eslick et al, 2002), increase the risk of reproductive disorders (Figura et al, 2002), and induce cerebral ischemia (Grau et al, 2001) and coronary heart disease (Pellicano et al, 1999). A screen of 50 patients with H. pylori infection has revealed 33.3% prevalence of anti-b2GPI antibodies (Sorice et al, 2000).…”
Section: Anti-b2gpi and Infectionmentioning
confidence: 99%
“…Hyperemesis gravidarum [8][9][10][11][12] Preeclampsia [13][14][15]23] Iron-deficiency Anemia [16][17][18][19] Intrauterine growth Restriction [20][21][22]27] Spontaneous abortion [24][25][26] and inflammatory damage over the gastric epithelium resulting in gastrointestinal disturbance such as hyperemesis gravidarum. H. pylori sequesters essential micronutrients from the host organism such as Iron (Fe) and it causes iron deficiency anemia.…”
Section: Referencementioning
confidence: 99%
“…In Australia in 2002, Eslick et al [21] observed an association with H. pylori infection and low birth weight for the first time and they showed that intra-uterine growth restriction was more common in H. pylori seropositive women (13.5%) compared to seronegative women (6.0%).…”
Section: Intrauterine Growth Restriction (Iugr)mentioning
confidence: 99%
“…Por outro lado, já foi sugerido ser a presença de infecção pelo H. pylori fator de risco para o desenvolvimento intra-uterino do feto 12 . Em nosso meio, raras são as pesquisas sobre a prevalência do H. pylori em gestantes 13 ; da mesma maneira, eventual correlação da positividade sorológica para anticorpos IgG do H. pylori com os sintomas dispépticos na gravidez e com diferentes caracterís-ticas maternas, ainda carece de investigação.…”
Section: Introductionunclassified